Analisis Pengaruh Media Utar dalam Metode Problem Based Learning Berdasarkan Capaian Belajar Keragaman Lingkungan Sekitar di SDN Pandeanlamper 04 - Sella Ferika Ferika; S. Sumarno; Ismartiningsih Ismartiningsih (Journal on Education, 2024)
This study aims to determine the impact of using the "smart snakes and ladders" educational media and the Problem Based Learning (PBL) model on the learning achievements of fifth-grade students at SDN Pandeanlamper 04. The results show that most students achieved better learning outcomes when using the educational media and the PBL model. The average scores for students who felt the method was influential reached 80, while those who felt it was less influential and ordinary were 75 and 68, respectively. These findings indicate that the use of varied educational media and the PBL model can enhance the quality of learning and active student participation. Thus, this approach can be used as a reference in efforts to improve the effectiveness of education in elementary schools.